Modeling the Effects of Grade Retention in High School - Bart Cockx; Matteo Picchio; Stijn Baert (Global Labor Organization (GLO), 2017)
A dynamic discrete choice model is set up to estimate the effects of grade retention in high school, both in the short-run (end-of-year evaluation) and in the long-run (drop-out and delay). In contrast to other evaluation approaches, this model captures essential treatment heterogeneity and controls for grade-varying unobservable determinants. In addition, forced track downgrading is considered as an alternative remedial measure. Our results indicate that grade retention has a neutral effect on academic achievement in the short-run. In the long-run, grade retention, just like forced downgrading, has adverse effects on schooling outcomes and, more so, for less able pupils.
Keywords: C33; C35; I21; 330; Education; grade retention; track mobility; dynamic discrete choice models; heterogeneous treatment effects